Analisa Penempatan Dan Kebutuhan Proteksi Katodik Pada Sistem Pipa Gas Bawah Laut Offshore Dari Pulau Pemping Ke Tanjung Uncang Batam - Nur Azisah; Daeng Paroka; Wahyuddin Wahyuddin (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
Corrosion is a problem that often occurs in submarine pipelines. This is because the metal pipe material is installed in environments that have a high level of corrosivity. Although corrosion cannot be avoided or eliminated, it can be controlled by cathodic protection. One of them is the sacrificial anode method. The aim of this research is to design a corrosion rate control in an underwater pipe along 13.5km, with a diameter of 16 inches for a design life of 45 years. The anode used is a 400 mm long and 40 mm thick anode made of aluminum alloy. In designing this cathodic protection, the writer refers to DNVGL-F103 and ISO 15589-2. From the results of this study, we will get the total anode needed to protect the pipe and the installation distance between the anodes. Based on the total anode, it can be seen the estimated cost needed in making cathodic protection.